Lessons learned from 10 years of experience with minimally invasive cardiac surgery - El-Sayed Ahmad, Ali; Salamate, Saad; Bakhtiary, Farhad (Frontiers in Cardiovascular Medicine, 2023)
Minimally invasive cardiac surgery gained gradually interest world-wide since its inception more than a quarter of a century ago. The need to offer patients smaller and better-tolerated incisions with high-quality clinical outcomes, particularly in structural heart disease, has become imperative to keep pace with the evolution of transcatheter valve implantation. We learned lessons from our experience in this field, especially in the endoscopic access via minithoracotomy. In order to improve the safety and efficacy of this endoscopic minimally access, we summarized and highlighted the lessons as a template for newly established cardiac surgeons in minimally invasive techniques.